Prediksi Hasil Ujian Kompetensi Mahasiswa Program Diploma Keperawatan - Rayendra, R (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Nursing Diploma Degree Student Competency Test which has been done since 2013 is still found by students who have not passed. This makes the nursing college conducting the competency test have to think of corrective steps so that in each period of the competency test there are no more students who do not pass. One way to do this is to make predictions on the results of the competency test using the Adaptive Neuro Fuzzy Inference System (ANFIS) Method. The data used are past data from the results of the Nabila Nursing Academy competency test results from 2015 to 2019 totaling 146 data. The variables used are gender, participation status, academic achievement index (GPA), and follow the tryout. For ANFIS training data were used 50 data and 96 data for testing data. Obtained a minimum error of 0.00% and a maximum error of 0.94% and a MAPE value of 0.11%. With a small MAPE value it can be concluded that ANFIS can predict the results of competency tests in nursing diploma degree students.